PEMANFAATAN FASILITAS PEMBELAJARAN - Muhammad Nuzli (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2021)
This research is motivated by the limitations of school’s facilities in improving the performance of Islamic Religious Education teachers. The purpose of this study is to determine the efforts to utilize learning facilities in improving the performance of Islamic Religious Education Teachers at the Integrated Islamic Elementary School of Nurul Balad, Mentawak Village, Nalo Tantan District, how to improve the performance of Islamic Religious Education Teachers at the Integrated Islamic Elementary School of Nurul Balad and the obstacles faced in improving the performance of Islamic Religious Education Teachers at the Integrated Islamic Elementary School of Nurul Balad, Mentawak Village, Nalo Tantan District. This study used descriptive qualitative method. The data obtained through the results of observations, interviews and documentations. The results showed that the efforts to utilize learning facilities in improving the performance of Islamic Religious Education Teachers at the Integrated Islamic Elementary School Nurul Balad Mentawak Village, Nalo Tantan District, namely the school attempted to provide learning facilities for Islamic Religious Education Teachers, according to the priority scale. The way to improve the performance of Islamic Religious Education Teachers at the Integrated Islamic Elementary School Nurul Balad Mentawak Village Nalo Tantan District is to instill a sense of responsibility that must be improved again, by continuously evaluating what is given to students both at the level of effectiveness and efficiency. The obstacle in the effort to utilize learning facilities in improving the performance of Islamic Religious Education Teachers at the Integrated Islamic Elementary School Nurul Balad, Mentawak Village, Nalo Tantan District, is more on the side of using teaching materials and the use of learning facilities that require costs that are not yet available.